Social Media Marketing and Brand Image as Determinant Factor of Purchase Decision - Abdillah, Fitriyadi; Nugraha, Aa Willy (Jurnal Ekonomi Manajemen Perbankan, 2024)
Marketing by using social media (social media marketing) has increased in this era. With the rapid development of technology, the internet has made it easier to access information and communicate across distances. This research aimed to analyze social media marketing and brand image on consumers’ purchase decisions of Mitra Emas Product of BJB Syariah Bank in Tasikmalaya Branch. The survey used a quantitative approach to explore the impact of independent variables on dependent variables. This study used 140 respondents as a sample with a simple random sample technique. The analytical technique was path analysis. This study showed that both social media marketing and brand image significantly impact consumers' purchase decisions of Mitra Emas products from BJB Syariah Bank, Tasikmalaya Branch, both individually and collectively.